2014
DOI: 10.1155/2014/354260
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heating and Cyclic Tension on the Induction of Heat Shock Proteins and Bone-Related Proteins by MC3T3-E1 Cells

Abstract: Stress conditioning (e.g., thermal, shear, and tensile stress) of bone cells has been shown to enhance healing. However, prior studies have not investigated whether combined stress could synergistically promote bone regeneration. This study explored the impact of combined thermal and tensile stress on the induction of heat shock proteins (HSPs) and bone-related proteins by a murine preosteoblast cell line (MC3T3-E1). Cells were exposed to thermal stress using a water bath (44°C for 4 or 8 minutes) with posthea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Studies have shown that fibroblasts and endothelial cells exposed to mild temperature stress (1 h at 41 °C) demonstrated slowed cell aging and an accelerated angiogenesis rate (Rattan et al, 2007). Furthermore, direct application of heat positively affects bone regeneration and mineralization and increases osteogenetic differentiation [ 19 , 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that fibroblasts and endothelial cells exposed to mild temperature stress (1 h at 41 °C) demonstrated slowed cell aging and an accelerated angiogenesis rate (Rattan et al, 2007). Furthermore, direct application of heat positively affects bone regeneration and mineralization and increases osteogenetic differentiation [ 19 , 20 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, fibroblasts and endothelial cells exposed to mild temperature stress (1 h at 41 °C) showed slowed cell ageing and an accelerated angiogenesis rate [ 18 ]. Direct application of heat also positively affects bone regeneration and mineralization [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…High expressions of HSP90-β and BMP-2 was a common phenomenon of physical treatments for OP. HSP90-β promotes osteogenesis by enhancing BMP-2 (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical loading may be another environmental stressor to cells especially for the cells that are found in the load bearing tissues. Hence, musculoskeletal cells such as chondrocytes, tendon fibroblasts and pre-osteoblasts, were shown to respond to mechanical stress by upregulating the expression of heat shock proteins (HSPs) 2 3 4 5 6 7 8 . Similarly, in cartilage tissues and osteocytes, ER stress markers were upregulated in response to mechanical stress 9 10 11 .…”
mentioning
confidence: 99%